Analisis Peran Negara dan Swasta dalam Pengelolaan Sektor Publik dalam Pengelolaan Sampah di Cilowong Provinsi Banten - Amanda Ester S; Eli Apud Saepudin; Azhra Nuha Salsabila; Siti Fadillah; Nurul Aini (MISTER: Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
Waste is a problem in Serang City that has yet to be addressed properly. It is proven that there are still many waste piles on the shoulders of the Serang City roads. This research aims to analyze the implementation and management of waste management based on the Local Regulation of Serang City. The Cilowong River, which crosses Serang City and Serang Regency, is polluted by waste. The pollution is caused by ineffective waste management. This study aims to analyze the condition of waste management in the Cilowong River. Data were collected through observation, interviews, and documentation. The results showed that the volume of waste in the Cilowong River is high, reaching 1,800 tons per day, exceeding the capacity of the Cilowong Final Processing Site (TPAS) which is only 800 tons per day. The waste management system has not been optimized, and there is still a lot of waste being dumped into the river. Lack of public awareness about the importance of keeping the environment clean is also a factor in pollution. This study recommends several solutions, such as Improving waste processing infrastructure. Implementation of a more effective waste management system, such as 3R (Reduce, Reuse, Recycle). Increased education and socialization to the community about the importance of maintaining environmental cleanliness